Carbon supported Ni1Pt1 nanocatalyst as superior electrocatalyst with increased power density in direct borohydride-hydrogen peroxide and investigation of cell impedance at different temperatures and discharging currents. (15th July 2017) - Hosseini, M.G.; Mahmoodi, R.; Sadeghi Amjadi, M.
Abstract: Carbon supported NiPt and Pt nanoparticles are synthesized using chemical reduction with sodium borohydride (NaBH4 ). The metal loading in synthesized nanocatalysts was 20 wt% and the ratio of Ni:Pt in the nanocatalysts was 1:1. The physical properties of nanocatalysts are investigated by Field Emission scanning electron microscopy (FE-SEM), energy-dispersive x-ray spectroscopy (EDX), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The electrocatalytic activity of the NiPt/C and Pt/C catalysts toward BH 4 − oxidation in alkaline media is investigated by means of cyclic voltammetry (CV), chronopotentiometry (CP), chronoamperometry (CA). The current densities are normalized respect to actual Pt loading in the nanocatalysts. Cyclic voltammograms show that the NiPt/C electrocatalyst has higher catalytic activity toward NaBH4 electrooxidation. A direct borohydride-hydrogen peroxide fuel cell (DBHPFC) is fabricated using Pt/C (0.5 mg cm −2 ) as cathodic catalyst and NiPt/C (1 mg cm −2 ) as anodic catalyst. The influence of cell temperature, sodium borohydride and hydrogen peroxide concentration on the I-V and I-P curves is investigated. The obtained maximum power density is 106.63 mW cm −2 at 60 °C, 1 M NaBH4 and 2 M H2 O2 . Impedance spectrums are taken in NaBH4 1 M + H2 O2 2 M. The impedance results show that with increasing temperature and discharging current, anodic and cathodic charge transfer resistance reduce. Graphical abstract: Highlights: PtNi/C and Pt/C electrocatalysts were synthesized using impregnation method. Activation energy for BH 4 − oxidation on PtNi/C is lower than that of on Pt/C. The maximum power density obtained in DBHFC was 106.63 mW cm −2 . Catalytic activity of PtNi/C for BH 4 − oxidation is higher than that of Pt/C.